Interwoven lives Indigenous mothers of Salish coast communities - Wellman, Candace (Washington State University Press, 2019)
A companion to the award-winning ""Peace Weavers,"" ""Interwoven Lives"" depicts the experiences of four additional intermarried Indigenous women who influenced mid-1800s settlement in the Bellingham Bay area, describing their native culture, ancestral history and traits, and descendants' destinies.